The safety of esophagojejunostomy via a transorally inserted-anvil method vs extracorporeal anastomosis using a circular stapler during total gastrectomy for Siewert type 2 adenocarcinoma of the esophagogastric junction. (11th October 2019) - Chen, Xin-Hua; Hu, Yan-Feng; Luo, Jun; Chen, Yue-Hong; Liu, Hao; Lin, Tian; Chen, Hao; Li, Guo-Xin; Yu, Jiang
Abstract: Background: Intracorporeal esophagojejunostomy via a transorally inserted-anvil method during laparoscopic total gastrectomy (LTG) for upper gastric cancer has been demonstrated to be feasible, but the use of this assessment exclusively for Siewert type 2 adenocarcinoma of the esophagogastric junction (AEG) has not been reported. Methods: A total of 428 consecutive gastric-cancer patients who underwent LTG in Nanfang Hospital from January 2008 to December 2016 were reviewed. Among these patients, 98 were classified as Siewert type 2 AEG. The patients underwent intracorporeal esophagojejunostomy through either a transorally inserted-anvil method ( n  =   27) or extracorporeal anastomosis usinga circular stapler ( n  =   71). After generating propensity scores with covariates that were associated with developing anastomotic leakage, 26 patients who underwent esophagojejunostomy via the transorally inserted-anvil method (transoral group) were 1:1 matched with 26 patients who underwent the procedure via extracorporeal anastomosis using a circular stapler (extracorporeal group). The safety after 30 days post-operatively was compared between the two groups. Results: The transoral group and extracorporeal group were balanced regarding the baseline variables. The operative time, reconstruction duration, number of dissected lymph nodes, length of the proximal resection margins, estimated blood loss, intra-operative complication rate, and post-operative recovery course were not significantly different between the two groups. The mean anvil-insertion completion time (9.7 ± 3.0 vs 13.4 ± 2.0   minutes, P  <   0.001) and the median incision length (5.5 vs 7.0   cm, P  <   0.001) in the transoral group were shorter than those in the extracorporeal group. The incidence of post-operative complications (26.9% vs 23.1%, P  =   0.749) and the classification of complication severity ( P  =   0.939) were similar between the two groups. Conclusions: Intracorporeal esophagojejunostomy through a transorally inserted-anvil method may be a potentially safe approach to simplify and optimize the procedure during LTG for Siewert type 2 AEG.